LOUISIANA CIVIL CODE AS A MEANS OF ESTABLISHING AND VERIFICATION OF TERMINOLOGICAL EQUIVALENCE FOR TRANSLATION AND LEXICOGRAPHY PURPOSES - ILUK, Łukasz (Comparative Legilinguistics, 2016)
The following article shows what from a legal point of view appears as more important in a translated term; either its fidelity or message. It includes reasons for literal translation of legal texts and the consequences of its unjustified use. Starting with the meaning of the Napoleonic codifications in English there appears a process of identifying and establishing functionally equivalent terms in the Polish civil code and the Louisiana civil code exemplified by the terminological field: drobne nakłady, nakłady konieczne, inne nakłady and naprawy konieczne. The analysis indicates that the legal comparison enables finding the right equivalent.